Good University Governance To Universities Performance: Systematic Literature Review - Kurnia Endah Riana; Rini Dwiyani Hadiwidjaja (Green Publisher Indonesia, 2024)
The implementation of Good University Governance (GUG) in higher education institutions has an impact on the performance of the respective institutions. GUG is a system that regulates and controls higher education institutions to create added value, benefiting all stakeholders. The objective of this research is to compile a systematic literature review scientifically, starting from data collection, selection, reading, and finally data analysis. This analysis relates to the study of GUG implementation's impact on higher education performance. The research method used in this study is a systematic literature review (SLR) approach on journal papers published from 2019 to 2023. There are three Research Questions (RQs) and three Quality Assessments (QAs) defined in this study. The impact of GUG on the performance of higher education institutions is positive and significant. The findings indicate that studies from 2019 to 2023 on the impact of GUG on performance have predominantly been conducted in public universities, using SEM PLS data analysis methods, with the